1989
DOI: 10.1212/wnl.39.6.825
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of multiple sclerosis

Abstract: We conducted a study of 145 persons with multiple sclerosis who had been identified in a 1970 survey and 145 friend controls, to investigate whether the development of MS was associated with exposure to uncommon viruses or an older age at infection with 1 or more common viruses. The most striking finding was a strong positive association for history of infectious mononucleosis (IM), suggesting older age at exposure to Epstein-Barr virus, the most common etiologic agent of IM. We also found significant positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 0 publications
4
67
0
1
Order By: Relevance
“…Interestingly, compelling evidence support the association of IM with elevated risk of MS occurrence [11][12][13][14]. Based on a recent updated meta-analysis evaluating a total of 18 clinical studies, the combined relative risk for development of MS after IM was estimated at 2.17 (95% CI 1.97-2.39; P < 10 À54 ) [15], while when analyzed in HLA-DRB1Ã15 carriers individuals with history of IM had a sevenfold increased risk of developing the disease [16].…”
Section: Epstein-barr Virusmentioning
confidence: 98%
“…Interestingly, compelling evidence support the association of IM with elevated risk of MS occurrence [11][12][13][14]. Based on a recent updated meta-analysis evaluating a total of 18 clinical studies, the combined relative risk for development of MS after IM was estimated at 2.17 (95% CI 1.97-2.39; P < 10 À54 ) [15], while when analyzed in HLA-DRB1Ã15 carriers individuals with history of IM had a sevenfold increased risk of developing the disease [16].…”
Section: Epstein-barr Virusmentioning
confidence: 98%
“…Epidemiological studies first reported a positive association between a history of IM and the occurrence of MS (50,56,58). A recent cohort study consisting of more than 25,000 Scandinavian patients with IM who were followed up for the occurrence of MS (56) and a meta-analysis of smaller previous studies on the association of IM and MS pointed out that individuals with a history of IM have a more-than-twofoldincreased risk of developing MS compared to subjects who acquired the virus without symptoms (74).…”
Section: Altered Immune Responses To Ebv In Multiple Sclerosismentioning
confidence: 99%
“…The studies frequently failed to blind laboratory procedures or describe their sources of cases and controls. Case-control studies Nine case-control studies were identified (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). One 'A', four 'B', two 'C' and two 'D' ratings were assigned (Tables 3, 4).…”
Section: Seroepidemiologymentioning
confidence: 99%
“…There were two 'D' studies (30,32). Operskalski et al (32) found that cases were much more likely than controls to report a history of IM (OR 17.0, 95% CI 2.0 to 81.8).…”
Section: Seroepidemiologymentioning
confidence: 99%
See 1 more Smart Citation